Beneficial regulation of vitamin D3-rich extract from the processing by-products of Penaeus sinensis on preosteoblastic MC3T3-E1 cells and improvement of bone health in VD-deficient mice. Issue 8 (29th March 2023) - Liu, Xinyan; Song, Ru; Wei, Rongbian; Zhao, Baoding; Chu, Yurou
Abstract : Vitamin D3-rich extract activated RANKL/OPG signaling pathway in MC3T3-E1 cells and improved bone remodeling in VD-deficient mice. Abstract : Vitamin D (VD) plays an important role in preventing osteoporosis. However, knowledge of the osteogenic effect of VD3 from shrimp processing by-products is limited. In this study, a VD3 -rich extract from Penaeus sinensis processing by-products was prepared by saponification and liquid–liquid extraction combined with solid phase extraction for purification. The activity of purified VD3 -rich extract (PPs-VD3 ) on MC3T3-E1, a preosteoblastic cell line, was determined. Furthermore, the improvement effect of PPs-VD3 on bone health of VD-deficient mice was investigated. PPs-VD3 stimulated the proliferation and differentiation of MC3T3-E1 cells. Compared to the same concentration of the VD3 standard, mineralization of MC3T3-E1 cells increased after 14 d or 21 d of PPs-VD3 treatment. Western blotting showed that PPs-VD3 significantly upregulated the protein levels of bone morphogenetic protein 2 and runt-related transcription factor 2 compared to the VD3 standard. Furthermore, PPs-VD3 treatment activated the receptor activator of nuclear factor-kappa B ligand (RANKL)/osteoprotegerin (OPG) signaling pathway in MC3T3-E1 cells, especially increased OPG expression was detected at day 3 to day 14 compared to the VD3 standard treatment. More than ten medium and long chain fatty acids were detected in PPs-VD3, of which n-3 polyunsaturated fatty acids (PUFA) constituted 38.83 ± 8.61%, and the n-3/n-6 PUFA ratio in PPs-VD3 was 2.84 ± 0.23. The femoral trabeculae number and thickness of VD-deficient mice increased after 3 weeks of PPs-VD3 treatment. The changes of parameters associated with bone resorption including parathyroid hormone, bone mineral density and tartrate resistant acid phosphatase revealed the contribution of PPs-VD3 treatment in improving bone remodeling in VD-deficient mice. Our results suggest that PPs-VD3 could have potential prospects in alleviating osteoporosis or promotion of bone health.